Quality diet indexes and risk of hepatocellular carcinoma: Findings from the Singapore Chinese Health Study. Issue 9 (6th November 2020) - Luu, Hung N.; Neelakantan, Nithya; Geng, Ting‐ting; Wang, Renwei; Goh, George Boon‐Bee; Clemente, Jose C.; Jin, Aizhen; van Dam, Rob M; Jia, Wei; Behari, Jaideep; Koh, Woon‐Puay; Yuan, Jian‐Min
Abstract: There is limited research on the effect of dietary quality on hepatocellular carcinoma (HCC) risk in populations with relatively high risk of HCC. Using data from Singapore Chinese Health Study, a prospective cohort study, of 63 257 Chinese aged 45 to 74, we assessed four diet‐quality index (DQI) scores: the Alternative Health Eating Index‐2010 (AHEI‐2010), Alternate Mediterranean Diet (aMED), Dietary Approaches to Stop Hypertension (DASH) and Heathy Diet Indicator (HDI). We identified 561 incident HCC cases among the cohort participants after a mean of 17.6 years of follow‐up. Cox proportional hazard regression model was used to estimate hazard ratio (HR) and 95% confidence interval (CI) for HCC in relation to these DQI scores. Unconditional logistic regression method was used to evaluate the associations between DQIs and HCC risk among a subset of individuals who tested negative for hepatitis B surface antigen (HBsAg). High scores of AHEI‐2010, aMED and DASH, representing higher dietary quality, were associated with lower risk of HCC (all P trend  < .05). Compared with the lowest quartile, HRs (95% CIs) of HCC for the highest quartile of AHEI‐2010, aMED and DASH were 0.69 (0.53‐0.89), 0.70 (0.52‐0.95) and 0.67 (0.51‐0.87), respectively. No significant association between HDI and HCC risk was observed. Among HBsAg‐negative individuals, similar inverse associations were observed, and the strongest inverse association was for aMED (HRQ4vsQ1 = 0.46, 95% CI: 0.23‐0.94, P trend = .10). These findings support the notion that adherence to a healthier diet may lower the risk of HCC, suggesting that dietary modification may be an effective approach for primary prevention of HCC. Abstract : What's new? Can improving the daily diet of high‐risk populations lower their risk of hepatocellular carcinoma (HCC)? In this large, prospective Asian study, the authors found that the answer is yes. Three different diet‐quality index (DQI) scores were associated with a significant drop in HCC risk, by as much as 30%. These included the AHEI‐2010, aMED, and DASH. These findings suggest that public‐health programs emphasizing dietary modification may offer an effective strategy for the prevention of HCC.